Thermal stimulated current response in cupric oxide single crystal thin films over a wide temperature range. (9th December 2016) - Yang, Kungan; Wu, Shuxiang; Yu, Fengmei; Zhou, Wenqi; Wang, Yunjia; Meng, Meng; Wang, Gaili; Zhang, Yueli; Li, Shuwei
Abstract: Cupric oxide single crystal thin films ( 26 nm) were grown by plasma-assisted molecular beam epitaxy. X-ray diffraction, Raman spectra and in situ reflection high-energy electron diffraction show that the thin films are 2 × 2 reconstructed with an in-plane compression and out-of-plane stretching. A thermal stimulated current measurement indicates that the electric polarization response is shown in the special 2D cupric oxide single crystal thin film over a wide temperature range from 130 K to near-room temperature. We infer that the abnormal electric response involves the changing of phase transition temperature induced by structure distortion, the spin frustration and the magnetic fluctuation effect of a short-range magnetic order, or the combined action of both of the two factors mentioned above. This work suggests a promising clue for finding new room temperature single phase multiferroics or tuning phase transition temperatures.